Family visit to the Children’s Museum of Costa Rica - Rodríguez, Keilyn (2015)
The article provides a comparison of family interactions in the Children’s Museum of Costa Rica, focused on pedagogical orientations related with two museological devices of The Earth exhibicion Hall named Erosion of the Earth and Life Clock. The results show differences in the behavior of the joint activity of family members, according to the individual characteristics of them and according to the design of museum devices.